Production and characterization of the sensor matrices for the Mu3e Tile detector - Nazarova, Elizaveta; Briggl, Konrad; Küpperbusch, Jan; Schultz-Coulon, Hans-Christian; Stankova, Vera; Steinkamp, Erik (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2026)
The goal of the Mu3e experiment at the Paul Scherrer Institute (PSI, Switzerland) is to search for the rare charged-lepton flavor-violating decay μ+→e+e+e−, the observation of which would be an unambigous sign of physics beyond the Standard Model. Aiming for an ultimate sensitivity of O(10−16), Mu3e has the potential to improve upon previous searches by up to four orders of magnitude. The scintillating tile detector is one of two timing systems for the Mu3e experiment. The detector consists of two stations shaped as hollow cylinders enclosing the beam pipe and is realized in a modular concept. The base unit of the tile detector is a sensor matrix consisting of 4 × 4 scintillating tiles and silicon photo-multipliers (SiPMs) mounted on a printed circuit board which connects the matrix to the readout electronics. We present the developed procedures for producing and assembling the individual detector components, along with the specialized tools used to wrap the scintillating tiles into laser-cut ESR foil and to glue the tiles onto the SiPM matrices. Furthermore, the SiPM matrix characterization, including the measurement of basic parameters like breakdown voltage, gain and dark noise, as well as the quality assurance process of the fully assembled tile matrices are presented. Finally, commissioning of the first assembled tile detector modules is discussed.